PENGALAMAN TERBAIK MENINGKATKAN KETERAMPILAN MENULIS ENDING TEKS NARRATIVE SISWA KELAS X IPA 2 SMA NEGERI 1 BATANG ANAI MELALUI GULA - MARJENNY MARJENNY (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
This best paper is aimed to know whether the use of Google Classroom as a Learning Management System (LMS), or Gula for short, can give significant effect cognitively, practically and affectively toward students’ skill in writing at Grade X MIPA 2 of SMAN 1 Batang Anai. The paper was a writer’s best practice. The research was conducted at XI MIPA 2 students of SMA Negeri 1 Batang Anai, which consisted of 32 students, in 2019/2020 academic year. The instrument of the paper was writing test. The data were analyzed by comparing students’ writing test before and after administering the strategy. Based on the result of the test and the writer’s observation, it was found that Gula gave significant effect toward students’ writing skill, especially in KD 4.2 namely writing an ending of a narrative text It was proved by the result of the test which showed that (1) the mean score of the students’ writing test was 82 higher than that which was 74, (2) students participated actively and collaborated integratively in teaching and learning process, (3) the media accommodated not only extrovert students but also introvert ones, (4) the teaching and learning process was fun and enjoyable, and (5) the media implemented multiliteracies in enhancing students’ character. Based on the result above, it is concluded that Gula could improve students’ writing skill significantly. Therefore, it is also suggested to English teachers at SMA level to apply this LMS as an alternative collaborative learning media in teaching writing in English especially and other subjects as well.